UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN KEREHAU (Callicarpa longifolia Lam.) TERHADAP MENCIT PUTIH - Eka Siswanto; Desy Nur Indah Sari; Supomo Supomo (Jurnal Ilmiah Manuntung, 2015)
Leaves kerehau (Callicarpa longifolia Lam.) is one of the plants used for the treatment of malaria, ulcers, diarrhea, treatment after delivery, and fever, by drinking boiled water. Report usage and security kerehau leaves are still very few. The purpose of this study to determine the potential for acute toxicity by determining the value of LD50 (Lethal Dose 50) in 4 dose-rise that dose I, II, III, and IV of the ethanol extract of the leaves kerehau against this mice. The Research. Pharmacologically using experimental methods using a completely randomized design pattern is undirectional in the selection of test animals, They are 25 mice were divided into five groups (5 mice each group), with observed 4 hours to determine the toxic symptoms and continued observation every 24 hours for 7 days to see death. Results from this study show from 4 dose levels, dose group I = 16g / kg, group II = 8g / kg, group III = 4g / kg and group IV = 2g / kg and control = 0.5 ml Na-CMC. Symptoms namely the observation of behavior and neuromuscular but not on observations of the autonomic nervous, respiratory, gastrointestinal, and skin. LD50 value obtained is expressed by the LD50 (16g / kg) were categorized as practically non-toxic (> 15g / kg)